Corrosion-Erosion Waste of Metals in the Duct System of the Recycling Aluminium Furnace - Liptakova, Tatiana; Jandacka, Jozef; Malcho, Milan; Vojsovicova, Michaela (Communications - Scientific letters of the University of Zilina, 2012)
The corrosion aggressiveness of the environment in the recycling aluminium furnace duct system is very high. Temperature is in the range from 300 to 900 °C and chemical composition of combustion varies according to treated aluminium waste and flue gas flow is turbulent. These conditions are very complicated for construction metal selection. The aim of the work is to investigate corrosion-erosion behaviour of various construction metals in the operating conditions of the duct system. The metals with different chemical composition (unalloyed construction steel, stainless steel and nickel based alloy) were tested by long time experiment in the real work conditions of the recycling aluminium furnace. The character and intensity of the materials corrosion attack after one year exposition are evaluated by gravimetric and metallographic analysis.